ICTAC Kinetics Committee recommendations for collecting experimental thermal analysis data for kinetic computations - Vyazovkin, Sergey; Chrissafis, Konstantinos; Di Lorenzo, Maria Laura; Koga, Nobuyoshi; Pijolat, Michèle; Roduit, Bertrand; Sbirrazzuoli, Nicolas; Suñol, Joan Josep (Thermochimica acta, 2014)
•Recommendations developed for collecting TG, DSC, and DTA data for successful kinetic analysis.•Focus is on preparing proper samples and selecting adequate experimental conditions.•Specific advice is offered for most common types of thermal processes, chemical and physical. The present recommendations have been developed by the Kinetics Committee of the International Confederation for Thermal Analysis and Calorimetry (ICTAC). The recommendations offer guidance for obtaining kinetic data that are adequate to the actual kinetics of various processes, including thermal decomposition of inorganic solids; thermal and thermo-oxidative degradation of polymers and organics; reactions of solids with gases; polymerization and crosslinking; crystallization of polymers and inorganics; hazardous processes. The recommendations focus on kinetic measurements performed by means of thermal analysis methods such as thermogravimetry (TG) or thermogravimetric analysis (TGA), differential scanning calorimetry (DSC), and differential thermal analysis (DTA). The objective of these recommendations is to assist a non-expert with collecting adequate kinetic data by properly selecting the samples and measurement conditions.